Dengue fever and building constructors in Klang Valley Malaysia - Tien-Choon, Toh; Ling-Wan, Pee; Kai-Chen, Goh; hun-chuen, Gui; Nadzirah, Zainordin; Chia-Kuang, Lee (2021)
Construction sites have frequently been reported as dengue hotspots due to poor work planning and execution, and the constructors are often to blame. The spread of viruses into surrounding areas suggested that construction sites are an important driver of long-term dengue transmission. Nonetheless, little is known about what constructors know about dengue fever and how they prevent the disease from spreading on construction sites. This study investigated the knowledge of dengue and dengue prevention practices of building constructors in Klang Valley, Malaysia. Mean ranking analysis and factor analysis were performed on quantitative data collected from 123 respondents via a questionnaire survey. The main findings of the knowledge of dengue revealed that building constructors were aware that ‘periodically emptying or drying out containers can prevent mosquitoes breeding’, ‘proper disposal of unwanted items capable of retaining water around the site can prevent mosquitoes breeding’, and ‘dengue haemorrhagic fever can be fatal’. Important dengue prevention practices used by building constructors included ‘properly disposing the waste from site’, ‘cleaning up the site area’, and ‘clearing out debris that may block water flow in drain or roof gutter’. The underlying knowledge of dengue was found to be related to awareness and attitudes, medical facts, dengue virology, occurrence factors, dengue entomology, and dengue control whereas the underlying dengue prevention practices were found related to prevention of mosquito bites, source reduction practice, prevention of dengue transmission, and prevention of mosquito breeding. Future research can build on this study to educate building constructors about dengue and dengue prevention.